BUDDHISM IN DOING INTERRELIGIOUS CONNECTION (Study in Mindfulness from Thich Nhat Hanh) - Abdul Mujib (UIN Sunan Kalijaga Yogyakarta, 2016)
Buddhism as religion which prioritizes human being is more open than otherreligions. In this paper, I examine how Buddhism relates to other religions which have theological concepts, even though Buddhism also has relation into social engagement. I also discuss how Buddhism as a way of life can philosophically encounters with other philosophical religions. Therefore, I view Buddhism as theology or philosophy and also as social in the same time. I will show that although Buddhism does not have concept of God, yet it can build interreligious relation with theistic religions. Therefore, socially engaged and interior dialogue (meditation) can be alternatives for Buddhists to do interreligious connection.